Enabling gender equality future generations of the global world - Rodriguez, Eunice; Wejnert, Barbara (Research in political sociology ;, 2015)
To challenge gender discrimination and to secure the world's prosperity and peace, we urgently need pro-girls and pro-women policies in the contemporary, globally developing world. Such policies could mark an era of building greater gender equality across the world by sheltering domains of women's well-being that are shown to decline. These needs can be best summarized by Kofi Annan, Secretary General of the United Nations in 2005: "When women are fully involved, the benefits can be seen immediately: families are healthier, they are better fed, their income, savings and reinvestment go up. And what is true for families is true of communities and, eventually, of whole countries." The desperately needed gender equality would honor women's place in the world, would greatly honor each country's political constituencies and enrich democratic institutions. This volume of Research in Political Sociology addresses a broad range of gender equality issues from women's status and opportunities at work, education, health, political participation, community involvement and global migration; from a vast domain of countries in Europe, America, Australia, Asia and Africa.